2012
DOI: 10.1371/journal.pone.0030711
|View full text |Cite
|
Sign up to set email alerts
|

Routine Antenatal Anti-D Prophylaxis in Women Who Are Rh(D) Negative: Meta-Analyses Adjusted for Differences in Study Design and Quality

Abstract: BackgroundTo estimate the effectiveness of routine antenatal anti-D prophylaxis for preventing sensitisation in pregnant Rhesus negative women, and to explore whether this depends on the treatment regimen adopted.MethodsTen studies identified in a previous systematic literature search were included. Potential sources of bias were systematically identified using bias checklists, and their impact and uncertainty were quantified using expert opinion. Study results were adjusted for biases and combined, first in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 22 publications
3
43
0
Order By: Relevance
“…To inform other parameter estimates for this simulation, we conducted an additional literature search to identify relevant systematic reviews of antenatal anti-D prophylaxis. Four relevant reviews [61][62][63][64] were identified. These reviews provided data on the probability estimates of the events used in the simulation study, including sensitisation and compliance rates.…”
Section: Simulation Study Of Clinical Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…To inform other parameter estimates for this simulation, we conducted an additional literature search to identify relevant systematic reviews of antenatal anti-D prophylaxis. Four relevant reviews [61][62][63][64] were identified. These reviews provided data on the probability estimates of the events used in the simulation study, including sensitisation and compliance rates.…”
Section: Simulation Study Of Clinical Effectivenessmentioning
confidence: 99%
“…Turner et al 63 Following the publication of the NICE TA156, Turner et al 63 revisited the effectiveness of RAADP for preventing sensitisation in pregnant RhD-negative women. This publication used alternative meta-analytic methods, which allow for the adjustment of both methodological limitations (internal biases) in the set of studies to be combined and differences in study design relative to the research question of interest (external biases).…”
Section: National Institute For Health and Care Excellence Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Then, if appropriate, a metaanalysis or qualitative assessment can be conducted, incorporating the information 5 . For example, a UK group combined 6 data from clinical trials with those from cohort studies in a metaanalysis to assess the effectiveness of anti-D, a drug given to some pregnant women to prevent them from producing antibodies against their babies. In this case, potential sources of bias, such as different clinics providing care for the women in cohort studies, were systematically identified, and their impact was minimized.…”
Section: Make Sense Of Health Datamentioning
confidence: 99%
“…2 Late anemia is a recognized complication of HDN regardless of the initial disease severity. 3 Now-a-days HDN is becoming less common, because of introduction of anti D antibodies, early intervention and specialty care centers. In this case report, we present a 24 day old infant born to an Rh negative mother with initial mild jaundice followed by late onset severe anemia.…”
Section: Introductionmentioning
confidence: 99%